Production Tribological Behavior Feature of Metallic Nanoparticle Additives; Applied Mechanics and Materials; Vol. 756 : Mechanical Engineering, Automation and Control Systems (MEACS2014) - Belyaev S. A. Sergey Aleksandrovich (Material Engineering and Technologies, 2015)
Title screen